2019
DOI: 10.1159/000500075
|View full text |Cite
|
Sign up to set email alerts
|

Daily Habit of Water Intake in Patients with Cerebral Infarction before its Onset; Comparison with a Healthy Population: A Cross-Sectional Study

Abstract: Background: While water intake is frequently recommended to prevent cerebral infarction (CI), only few studies have been published on this topic. Objectives: This study retrospectively estimated the daily non-alcohol drink (NAD) intake in CI patients before CI onset and compared it with NAD in healthy subjects. Methods: We performed a cross-sectional study on CI patients in 3 hospitals and healthy subjects in the Kobe Orthopedic and Biomedical Epidemiologic (KOBE) study. Data from 1,287 subjects (274 CI patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Accordingly, the occurrence of ischemic stroke has been reported to rise with decreasing temperature [18] and its incidence does not vary significantly with season [19,20]. Moreover, we also demonstrated a positive association between a lesser NAD intake habit and CI after adjusting for the effect of the seasonal change [3]. These findings strongly indicated maintaining sufficient water intake for prevention of CI due to dehydration not only in summer but also throughout the year is important.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Accordingly, the occurrence of ischemic stroke has been reported to rise with decreasing temperature [18] and its incidence does not vary significantly with season [19,20]. Moreover, we also demonstrated a positive association between a lesser NAD intake habit and CI after adjusting for the effect of the seasonal change [3]. These findings strongly indicated maintaining sufficient water intake for prevention of CI due to dehydration not only in summer but also throughout the year is important.…”
Section: Introductionsupporting
confidence: 61%
“…In contrast to most developed countries, the event risks of cerebrovascular diseases are high and it remains one of top-ranked causes of death and disability in Japan [1,2]. Recent studies demonstrated that patients with cerebral infarction (CI) took less water before the onset than healthy subjects [3], and higher water intake reduced mortality due to ischemic stroke [4,5,6,7,8]. The potential association between water intake and CI is generally explained via the following pathophysiological mechanism; 1) insufficient hydration is one of the most important factors causing dehydration and 2) dehydration is considered to be associated with the development of cerebral ischemic events [7,9,10], probably because of vascular collapse [11], increased blood viscosity [12], and spasm [13].…”
Section: Introductionmentioning
confidence: 99%